Analysis of the Service Quality of Electronic Identity Card (e-KTP) Administration at the Sub-District Office of Kundur District, Karimun Regency - Anggraini Fadillah; Sri Maulidiah (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
This study aims to analyse the quality of administrative services for Electronic Identity Card (KTP-el) issuance at the Sub-district Office of Kundur, Karimun Regency, and to identify the inhibiting factors in its implementation. The research employs a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. Data analysis is based on the five SERVQUAL dimensions proposed by Fandy Tjiptono, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The findings indicate that the overall service quality is fairly good, yet still not optimal. Major obstacles include limited infrastructure (such as the number of computers and lack of disability access), the absence of a digital queuing and document tracking system, lack of formal complaint mechanisms, and a high workload among staff. The study recommends the development of technology-based service systems, regular training and certification for service personnel, additional human resources, and the establishment of complaint mechanisms and periodic customer satisfaction surveys. These findings are expected to provide input for local governments in improving the quality of public services, particularly in border and island regions.